Telaah Komunikasi Orang Tua dan Anak Menurut Hudzaifah Ahmad Akash dalam Kitab Asrar Tarbiyah Al Awlad - Kinanthi Nur Fikriya; Choirun Nisa; Amin Subakti (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
A good relationship between parents and children is seen from the way of communication between the two. If parents know and implement good communication, a happy family atmosphere will be created. The aim of this scientific work is to find out good ways of communicating for parents with their children. In conducting this research, we used the library research method with the main source in the book Asra>r Tarbiyah Al-Awlad by Hudzaifah Ahmad Akash. To analyze existing data using the content analysis method. The results of this research are related to the way parents communicate with their children, namely by expressing love, good communication, giving appropriate criticism and praise, and instilling positive words in children.